Silicone rubber composite fine particles, thermosetting resin composition containing the silicone rubber composite fine particles, and cured product of the composition, and article

CN122941177APending Publication Date: 2026-10-20NISSHIN CHEM IND CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202610427876.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-04-11
Filing Date
2026-04-02
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

然而,由于丙烯酸树脂、硅酮的壳部分没有与环氧树脂化学键合,因此密合性低,而且由于丙烯酸树脂的Tg在环氧树脂固化温度以下,因此存在熔融凝聚而不能均匀分散的可能性,仍有改进的空间

Benefits of technology

本发明的复合微粒具有硅橡胶的柔软性,并且对固化物赋予选自二氧化硅、氮化硼和氮化铝中的至少1种无机粉体所具有的低介质损耗角正切。通过将包含上述无机粉体的复合微粒掺混于热固性树脂、特别是环氧树脂中,与将上述无机粉体单独混合于热固性树脂中相比,可供给弯曲弹性模量等机械特性优异的固化物。该本发明的热固性树脂组合物适合作为单层树脂片、层叠树脂片、预浸料、覆金属箔层叠板、印刷布线板、密封用材料、纤维强化复合材料和粘接剂。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

This invention relates to silicone rubber microparticles, and particularly aims to provide silicone rubber microparticles that possess the softness of silicone rubber, do not aggregate in thermosetting resins, mix well with thermosetting resins, and provide cured products with low dielectric constant and low dielectric loss tangent. A silicone rubber composite microparticle, having an average particle size of 0.1 to 100 μm, comprises: a composite containing (A) silicone rubber particles and (B) at least one inorganic powder selected from silica, boron nitride, and aluminum nitride; and (C) a condensate of an organoalkoxysilane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] One aspect of the present invention relates to silicone rubber composite microparticles. In particular, it relates to silicone rubber composite microparticles that possess the flexibility of silicone rubber and do not aggregate in thermosetting resins, imparting a low dielectric constant / low dielectric loss tangent to the cured product, and thermosetting resin compositions comprising the composite microparticles, as well as single-layer resin sheets, laminated resin sheets, prepregs, metal-coated laminates, printed wiring boards, sealing materials, fiber-reinforced composite materials, and adhesives. Background Technology

[0002] For a long time, resin sealing has been the mainstream method for sealing electronic components such as transistors and ICs, considering factors such as productivity and cost. Epoxy resins, which offer a good balance of electrical properties, moisture resistance, heat resistance, mechanical properties, and adhesion to inserts, are primarily used for sealing. However, due to the hardness and brittleness of epoxy resins, modifications to the epoxy resin itself or the addition of stress-relieving additives are necessary for its sealing applications.

[0003] Acrylic rubber, epoxy-modified silicone oil, amino-modified silicone oil, and silicone rubber powder are commonly known additives for stress mitigation. However, acrylic rubber lacks chemical reaction sites with epoxy, resulting in poor adhesion. Furthermore, epoxy-modified and amino-modified silicone oils have low molecular weights, leading to insufficient stress mitigation. Silicone rubber powder exhibits poor compatibility with epoxy resin, resulting in difficulty in uniform dispersion.

[0004] For example, Japanese Patent Application Publication No. 2007-23061 discloses an epoxy resin composition obtained by adding an epoxy-modified low molecular weight silicone to an epoxy resin to improve its flowability. However, due to the poor compatibility between the epoxy-modified low molecular weight silicone and the epoxy resin, it is difficult to uniformly mix the silicone with the epoxy resin if a sufficient amount is added in an attempt to obtain a stress-relieving effect.

[0005] Japanese Patent Application Publication No. 2018-172545 discloses a solid sealing material for compression molding comprising epoxy resin and epoxy-modified silicone, which achieves excellent stability in warpage behavior. However, based on this alone, the stress relief effect is not sufficient, and there is still room for improvement.

[0006] Furthermore, in Japanese Patent Application Publication No. 2007-146148, a reduction in elastic modulus was achieved by adding a core-shell silicone compound with a silicone oil core and an organic polymer such as acrylic resin as the shell to epoxy resin. In Japanese Patent Application Publication No. 8-85753, dispersibility was improved by adding silicone microparticles coated with organosilicon silsesquioxane resin onto silicone rubber spherical microparticles to epoxy resin. However, since the shell portion of the acrylic resin and silicone is not chemically bonded to the epoxy resin, the adhesion is low. Moreover, because the Tg of the acrylic resin is below the curing temperature of the epoxy resin, there is a possibility of melting and agglomeration, resulting in uneven dispersion; therefore, there is still room for improvement.

[0007] Japanese Patent Application Publication No. 2021-75605 discloses epoxy-modified silicone microparticles that possess the flexibility of silicone rubber, do not aggregate in thermosetting resins, and exhibit excellent adhesion to thermosetting resins. However, there is a need to develop further stress-relieving additives.

[0008] Existing technical documents Patent documents Patent Document 1: Japanese Patent Application Publication No. 2007-23061 Patent Document 2: Japanese Patent Application Publication No. 2018-172545 Patent Document 3: Japanese Patent Application Publication No. 2007-146148 Patent Document 4: Japanese Patent Application Publication No. 8-85753 Patent document 5: Japanese Patent Application Publication No. 2021-75605. Summary of the Invention

[0009] The problem that the invention aims to solve The present invention was made in view of the above circumstances and relates to a silicone rubber microparticle, with a particular objective of providing: silicone rubber microparticles having the flexibility of silicone rubber and not agglomerating in thermosetting resins, being well mixed with thermosetting resins, and supplying a cured product with properties of low dielectric constant and low dielectric loss tangent.

[0010] Methods for solving problems To achieve the above objectives, the inventors conducted in-depth research and discovered that silicone rubber composite microparticles containing at least one inorganic powder selected from silicon dioxide, boron nitride, and aluminum nitride possess the characteristics of silicone rubber and do not aggregate in thermosetting resins. They exhibit good dispersibility relative to thermosetting resins, thereby supplying a cured product with low dielectric constant and low dielectric loss tangent, thus completing the present invention.

[0011] That is, one aspect of the present invention provides: [1] A silicone rubber composite microparticle, comprising: silicone rubber composite microparticles having an average particle size of 0.1~100 μm, and comprising: A composite containing (A) silicone rubber particles and (B) at least one inorganic powder selected from silicon dioxide, boron nitride, and aluminum nitride; and (C) Condensates of organoalkoxysilanes.

[0012] Another aspect of the present invention provides silicone rubber composite microparticles having the following configuration or a method for manufacturing the silicone rubber composite microparticles.

[0013] [2] The silicone rubber composite microparticles described in [1] above, wherein, relative to 100% by mass of the silicone rubber composite microparticles, they comprise: 0.1~80% by mass of (A) silicone rubber granules; 0.1 to 80% by mass of (B) is selected from at least one inorganic powder chosen from silicon dioxide, boron nitride, and aluminum nitride; and Condensates of (C) organoalkoxysilanes, ranging from 0.1% to 80% by mass. [3] The silicone rubber composite microparticles described in [1] or [2] above, wherein the silicone rubber of component (A) has the structure represented by the following formula (1), -(R 1 2SiO) a - (1) In the above formula (1), R 1 Each group consists of a substituted or unsubstituted monovalent hydrocarbon group having 1 to 20 carbon atoms, and a is an integer from 5 to 5,000.

[0014] [4] The silicone rubber composite microparticles described in any one of [1] to [3] above, wherein the (C) organoalkoxysilane is at least one selected from the group consisting of trialkoxysilane represented by the following general formula (2) and tetraalkoxysilane represented by the following general formula (3). R 2 Si(OR 3 )3 (2) Si(OR 3 )4 (3) In equations (2) and (3) above, R 2 R is a monovalent hydrocarbon group with 1 to 20 carbon atoms. 3 It is an alkyl group having 1 to 6 carbon atoms.

[0015] [5] The silicone rubber composite microparticles described in any one of [1] to [4] above, wherein the silicone rubber composite microparticles are composed of the following components: (A) a composite of silicone rubber particles and (B) at least one inorganic powder selected from silicon dioxide, boron nitride and aluminum nitride; and (C) a condensate of an organoalkoxysilane.

[0016] [6] A thermosetting resin composition comprising a thermosetting resin and silicone rubber composite microparticles as described in any one of [1] to [5] above, wherein the amount of the silicone rubber composite microparticles is 0.5 to 80 parts by weight relative to 100 parts by weight of the thermosetting resin.

[0017] [7] A cured product which is formed by curing the thermosetting resin composition described above [6].

[0018] [8] A semiconductor element sealed with the curing agent described in [7] above.

[0019] [9] A method for manufacturing silicone rubber composite microparticles, the method comprising: The process of mixing (A') a cured organopolysiloxane composition, (B) at least one inorganic powder selected from silica, boron nitride, and aluminum nitride, water, and optionally a surfactant, to cure the cured organopolysiloxane composition to obtain an aqueous dispersion of the composite; and The process involves hydrolyzing and condensing (C) organoalkoxysilanes in the aqueous dispersion of the composite obtained in the process to obtain silicone rubber composite microparticles with an average particle size of 0.1 to 100 μm.

[0020]

[10] In the method for manufacturing silicone rubber composite microparticles described above [9], the amount of component (B) is 0.1 to 80 parts by mass relative to a total of 100 parts by mass of the organic polysiloxane, inorganic powder and organic alkoxysilane in component (A'), and the amount of organic alkoxysilane is 0.1 to 80 parts by mass.

[0021]

[11] The method for manufacturing silicone rubber composite microparticles described in [9] or

[10] above, wherein the (A') curing organopolysiloxane composition is a condensation reaction curing organopolysiloxane composition, a free radical reaction curing organopolysiloxane composition, or an addition reaction curing organopolysiloxane composition.

[0022]

[12] The method for manufacturing silicone rubber composite microparticles according to any one of [9] to

[11] above, wherein the (C) organoalkoxysilane is at least one selected from the group consisting of trialkoxysilane represented by the following general formula (2) and tetraalkoxysilane represented by the following general formula (3). R 2 Si(OR 3 )3 (2) Si(OR 3 )4 (3) In equations (2) and (3) above, R 2 R is a monovalent hydrocarbon group with 1 to 20 carbon atoms. 3 It is an alkyl group having 1 to 6 carbon atoms.

[0023] Invention Effects The composite microparticles of the present invention possess the flexibility of silicone rubber and impart a low dielectric loss tangent to the cured product, characteristic of at least one inorganic powder selected from silica, boron nitride, and aluminum nitride. By incorporating the composite microparticles containing the aforementioned inorganic powders into thermosetting resins, particularly epoxy resins, a cured product with superior mechanical properties such as flexural modulus can be supplied compared to mixing the aforementioned inorganic powders alone into the thermosetting resin. The thermosetting resin composition of the present invention is suitable as a single-layer resin sheet, a laminated resin sheet, a prepreg, a metal foil-coated laminate, a printed wiring board, a sealing material, a fiber-reinforced composite material, and an adhesive. Detailed Implementation

[0024] The present invention will now be described in more detail.

[0025] The silicone rubber composite microparticles of the present invention are silicone rubber composite microparticles with an average particle size of 0.1 to 100 μm formed by coating a composite containing (A) silicone rubber particles and (B) at least one inorganic powder selected from silicon dioxide, boron nitride and aluminum nitride with a condensate of (C) organoalkoxysilane.

[0026] A composite containing (A) silicone rubber particles and (B) at least one inorganic powder selected from silicon dioxide, boron nitride and aluminum nitride is a composite microparticle obtained by adding the aforementioned inorganic powder during the manufacture of silicone rubber particles.

[0027] (A) The silicone rubber of the silicone rubber particles preferably has linear organopolysiloxane blocks in the molecular structure shown in the following general formula (1), and is composed of spherical silicone curing material with rubber elasticity.

[0028] -(R 1 2SiO) a - (1) In the above formula (1), R 1It is a monovalent hydrocarbon group with 1 to 20 carbon atoms, either substituted or unsubstituted, or a group selected from organic groups containing reactive groups such as epoxy, amino, mercapto, acryloyloxy, and methacryloyloxy. Examples of monovalent hydrocarbon groups with 1 to 20 carbon atoms include alkyl groups such as methyl, ethyl, propyl, and butyl; aryl groups such as phenyl and tolyl; alkenyl groups such as vinyl and allyl; and aralkyl groups such as β-phenylethyl and β-phenylpropyl. The number of carbon atoms is preferably 1 to 10, more preferably 1 to 6. Furthermore, examples of substituted groups include groups in which some or all of the hydrogen atoms bonded to the carbon atoms of the aforementioned hydrocarbon group are replaced with halogen atoms, for example, monovalent haloalkyl groups such as chloromethyl and 3,3,3-trifluoropropyl. Preferably, R... 1 More than 90 mol% of it can be methyl.

[0029] In the above formula (1), a is an integer from 5 to 5,000, preferably a number from 10 to 1,000. If a is less than 5, the characteristics of linear organopolysiloxane cannot be fully expressed, and the effect of internal stress relief cannot be fully obtained. In addition, there is no special specification for the maximum value of a, but in practice, if it is greater than 5,000, the manufacture of silicone rubber particles will become difficult.

[0030] (A) Silicone rubber particles may contain silicone oil, organosilanes, inorganic powders other than component (B), organic powders, etc. The silicone rubber particles need to have an average particle size of 0.1 to 100 μm, preferably 1 to 30 μm. If the average particle size of the silicone rubber particles is less than the lower limit mentioned above, the particle flowability may decrease and the cohesiveness may increase. Furthermore, if the average particle size exceeds the upper limit mentioned above, it may impair the properties of the substrate. It should be noted that in this invention, the average particle size refers to the volume-based average particle size measured using a laser diffraction particle size distribution measuring device.

[0031] Examples of manufacturing the aforementioned silicone rubber particles include: condensation reactions of methoxysilyl (≡SiOCH3) and hydroxysilyl (≡SiOH), free radical reactions of mercaptosilyl (≡SiSH) and vinylsilyl (≡SiCH=CH2), and addition reactions of vinylsilyl (≡SiCH=CH2) and ≡SiH groups. From the perspectives of reactivity and reaction procedures, manufacturing based on addition reactions is preferred.

[0032] The silicone rubber composite microparticles of the present invention can be obtained by a manufacturing method comprising the following steps: mixing (A') the above-described curable organopolysiloxane composition, (B) at least one inorganic powder selected from silica, boron nitride, and aluminum nitride, water, and optionally a surfactant, and curing the addition-reaction-curable organopolysiloxane composition to obtain an aqueous dispersion of the composite (microparticles); and subjecting (C) an organoalkoxysilane to a hydrolytic condensation reaction in the aqueous dispersion of the composite to obtain silicone rubber composite microparticles having an average particle size of 0.1 to 100 μm. As described above, the (A') curable organopolysiloxane composition can be categorized as a condensation-reaction-curable organopolysiloxane composition, a free radical-reaction-curable organopolysiloxane composition, or an addition-reaction-curable organopolysiloxane composition. For example, an addition-reaction-curable organopolysiloxane composition is preferred, which is cured by an addition reaction of (a1) a vinyl-containing organopolysiloxane and (a2) an organohydrogen-containing organosiloxane in the presence of (a3) ​​a platinum-based catalyst. Relative to the total of 100 parts by mass of components (A'), (B) and (C), the amount of component (B) is 0.1 to 80 parts by mass, preferably 0.1 to 50 parts by mass, more preferably 1 to 30 parts by mass, and the amount of organoalkoxysilane (C) can be 0.1 to 80 parts by mass, preferably 10 to 80 parts by mass.

[0033] The silicone rubber composite microparticles of the present invention have an average particle size of 0.1 to 100 μm, preferably 1 to 30 μm, and more preferably 1 to 20 μm. If the average particle size of the silicone rubber composite microparticles is less than the lower limit mentioned above, the particle flowability may decrease and the cohesiveness may increase. Furthermore, if the average particle size exceeds the upper limit mentioned above, the properties of the substrate may be impaired. It should be noted that in the present invention, the average particle size refers to the volume-based average particle size measured using a laser diffraction particle size distribution measuring device.

[0034] In addition-reaction cured organopolysiloxane compositions, component (a1) is the main component of the organopolysiloxane supplied to the silicone rubber particles, and is cured by an addition reaction between component (a2) and component (a3) ​​catalyzed by component (a3). Component (a1) needs to have at least two vinyl groups bonded to silicon atoms in one molecule; these vinyl groups can be present in any part of the molecule, but are preferably present at least at the ends of the molecule. Examples of organic groups bonded to silicon atoms other than vinyl groups include those related to the R group. 1 The same group, preferably, is methyl at least 90 mol% of the organic group. In addition, (a1) the molecular structure of the vinyl-containing organopolysiloxane can be linear, branched, or a mixture thereof, and there is no particular limitation on the molecular weight, but in order to make the cured product a rubber-like elastomer, it is preferred to have a viscosity of 1 cP or more at 25°C.

[0035] Regarding component (a1), examples include linear, cyclic, or branched organopolysiloxanes represented by the following formula. In the above formula, b and c satisfy b+c=3 and are integers from 0 to 3, d is a positive number, e is 0 or a positive number, and 2b+e≥2; In the above formula, f is a positive number greater than 2, g is 0 or a positive integer, and f+g is 4 to 8; In the above formula, h is 1, 2 or 3, i is 0, 1 or 2, and h+i=3, j, k and L are positive numbers.

[0036] Component (a2) is a crosslinking agent for component (a1). The hydrogen atoms bonded to silicon atoms in this component (hereinafter, sometimes also referred to as hydrosilyl) undergo an addition reaction with the vinyl groups in component (a1) through the action of the catalyst (a3), thus solidifying the component. Therefore, component (a2) needs to have at least two hydrogen atoms bonded to silicon atoms in one molecule. Additionally, besides these hydrogen atoms, the organic groups bonded to silicon atoms must be derived from the aforementioned R... 1 The selected groups from the monovalent organic groups in the examples are acceptable. Preferably, 90 mol% or more of the organic groups bonded to silicon atoms are methyl groups. The molecular structure of component (a2) is not particularly limited; it can be linear, branched, or cyclic, or a mixture thereof. The molecular weight is not particularly limited, but for good compatibility with component (a1), a viscosity of 1 to 10,000 cP at 25°C is preferred.

[0037] Regarding the amount of component (a2), it is acceptable as long as the ratio of the number of hydrogenated silanes in component (a2) to the number of vinyl groups in component (a1) is 0.5 to 20, preferably 0.5 to 5. If the amount of component (a2) is less than the lower limit mentioned above, it is difficult to obtain good curing properties. In addition, if the amount of component (a2) exceeds the upper limit mentioned above, the physical properties of the cured rubber will decrease, which is not preferred.

[0038] As a component of (a2), examples include linear, cyclic, or branched polyorganohydrosiloxanes represented by the following formula. In the formula, m is 0 or 1, n is 2 or 3, and m + n = 3, p is 0 or a positive number, q is 0 or a positive number, and 2m + q ≥ 2; In the formula, r is a positive number greater than 2, s is 0 or a positive number, and r+s is 4 to 8; In the formula, t is 1, 2 or 3, u is 0, 1 or 2, and (t+u)=3, v, w and x are positive numbers.

[0039] Component (a3) ​​is a catalyst that enables the addition reaction between the silicon-bonded vinyl groups of component (a1) and the hydride silyl groups of component (a2). It can be appropriately selected from conventionally known addition reaction catalysts. Examples include platinum-based catalysts such as platinum-supported carbon or silica, chloroplatinic acid, platinum-olefin complexes, platinum-alcohol complexes, platinum-phosphorus complexes, platinum-vinylsiloxane complexes, and platinum coordination compounds.

[0040] Regarding the amount of component (a3), any amount sufficient to catalyze the above addition reaction is acceptable, but it is preferable that the amount of platinum atoms relative to component (a1) be in the range of 1 to 100 ppm. If it is less than 1 ppm, not only will the curing be slower, but it will also be more susceptible to catalyst toxicity. On the other hand, even if it exceeds 100 ppm, it is not particularly desirable to expect an improvement in the curing speed, which is not economical.

[0041] Examples of methods for curing the aforementioned silicone in an emulsion include: mixing a specified amount of (a1) a vinyl-containing organopolysiloxane and (a2) an organohydrogen-containing organopolysiloxane to prepare an organopolysiloxane composition; then adding water and a surfactant to the resulting composition and emulsifying it using a commercially available homogenizer or similar device.

[0042] In the process of curing the aforementioned silicone in an emulsion, it is preferable to add at least one inorganic powder selected from silica, boron nitride, and aluminum nitride to (a1) a mixture containing vinyl organopolysiloxane and (a2) organohydrogen polysiloxane, mix, and emulsify. This yields a composite (microparticles).

[0043] (B) At least one inorganic powder selected from silicon dioxide, boron nitride, and aluminum nitride may be a commercially available product. Examples of silicon dioxide include 0.1 to 100 μm spherical particles: WR Grace & Co.'s "SYLOBLOC", "SYLOID", and "SYLOJET"; Fuji Silysia Chemical, Ltd.'s "SYLYSIA" (silicon dioxide powder); DSL JAPAN Co., Ltd.'s "Carplex"; and AGC Si-Tech Co., Ltd.'s "SUNSPHERE". Examples of boron nitride include 0.1 to 100 μm flake-like to spherical particles: DENKA's SP-2 and SP-3. Examples of aluminum nitride include 0.1 to 100 μm flake-like to spherical particles: HF-01D, HF-05, and HF-20 (all manufactured by Tokuyama Co., Ltd.).

[0044] Regarding the amount of inorganic powder (B) in the silicone rubber composite microparticles, the content of inorganic powder in 100% by mass of the silicone rubber composite microparticles is preferably 0.1% to 80% by mass, more preferably 0.1% to 50% by mass, and even more preferably 1% to 30% by mass. Furthermore, regarding the amount of silicone rubber particles (A) in the silicone rubber composite microparticles, the content of silicone rubber particles (excluding (B) component) in 100% by mass of the silicone rubber composite microparticles is preferably 0.1% to 80% by mass, more preferably 10% to 80% by mass, and even more preferably 40% to 70% by mass.

[0045] As the surfactant mentioned above, nonionic surfactants such as polyoxyethylene alkylphenyl ethers, polyoxyethylene alkyl ethers, polyoxyethylene sorbitan fatty acid esters, and glycerol fatty acid esters are preferred, but anionic surfactants are also acceptable. The amount of surfactant added relative to 100 parts by weight of the emulsion can range from 0.01 to 20 parts by weight, preferably from 0.05 to 10 parts by weight. If the amount is less than the lower limit, it may be impossible to form fine particles from the composite particles. If the amount exceeds the upper limit, it may be difficult for the (C) organoalkoxysilane condensate to exist on the surface (outermost layer) of the composite (particles) containing silicone rubber particles and inorganic powder, or between the silicone rubber particles and the inorganic powder (interface). It should be noted that the 100 parts by weight of the emulsion mentioned above refers to a total of 100 parts by weight of the organopolysiloxane composition, inorganic powder, water, and surfactant.

[0046] By adding platinum-based catalyst (a3) ​​to the above emulsion, the above-mentioned organopolysiloxanes (a1) and (a2) are cured to prepare a dispersion of cured silicone rubber. As the platinum-based catalyst, a known reaction control agent can be added, or, if the platinum-based catalyst and reaction control agent are difficult to disperse in water, a surfactant can be used to make them water-dispersible before addition. Thus, an aqueous dispersion of composite microparticles obtained from the above-mentioned (A) silicone rubber particles and the above-mentioned (B) inorganic powder can be obtained.

[0047] Surfactants can be added to this aqueous dispersion. Adding surfactants improves the dispersibility of the complexes (particles) contained in the aqueous dispersion. Furthermore, the condensate of (C) organoalkoxysilanes (described later) can uniformly coat the surface of the complexes (particles). There are no particular limitations on the type of surfactant; appropriate selections can be made from conventionally known substances. Examples include: cationic surfactants such as quaternary ammonium salts and alkylamine salts; amphoteric surfactants such as alkyl betaines; nonionic surfactants such as polyoxyethylene alkyl ethers, polyoxyethylene alkylphenyl ethers, sorbitan fatty acid esters, and glycerol fatty acid esters; and anionic surfactants such as organic sulfonates and alkyl sulfate esters. One or more of these surfactants can be used in combination.

[0048] In the silicone rubber composite microparticles of the present invention, the condensate of an organoalkoxysilane may exist on the surface (outermost layer) of the composite (microparticles) comprising the aforementioned silicone rubber particles and inorganic powder, and between the aforementioned silicone rubber particles and inorganic powder (interface), either or both. An organoalkoxysilane (C) and an alkaline substance or alkaline aqueous solution, as needed, are added to an aqueous dispersion of the aforementioned composite (microparticles) and mixed to allow the organoalkoxysilane to undergo hydrolysis and condensation reactions, thereby forming an organoalkoxysilane condensate on the surface (outermost layer) of the composite (microparticles) and / or between the silicone rubber particles and inorganic powder (interface), thus obtaining the silicone rubber composite microparticles of the present invention. Preferably, the silicone rubber composite microparticles include a configuration where the organoalkoxysilane condensate covers a portion of the surface (outermost layer) of the composite (microparticles), and a configuration where the organoalkoxysilane condensate covers the entire surface (outermost layer) of the composite (microparticles), and more preferably, a configuration where the organoalkoxysilane condensate covers 20% to 100% of the surface of the composite (microparticles). In these schemes, condensates of organoalkoxysilanes can also exist between silicone rubber particles and inorganic powders (interface).

[0049] The silicone rubber composite microparticles of the present invention are more preferably silicone rubber composite microparticles composed only of the above-mentioned silicone rubber particles and inorganic powder composites (microparticles) and (C) condensates of organic alkoxysilanes.

[0050] The process of obtaining silicone rubber composite microparticles composed of the above-mentioned composite (microparticles) and the condensate of (C) organoalkoxysilane can also be carried out in the presence of an alkaline substance or an alkaline aqueous solution. The alkaline substance or alkaline aqueous solution can be any substance as long as it catalyzes the hydrolysis-condensation reaction of (C) organoalkoxysilane. Examples include: alkali metal hydroxides such as potassium hydroxide, sodium hydroxide, and lithium hydroxide; alkaline earth metal hydroxides such as calcium hydroxide and barium hydroxide; alkali metal carbonates such as potassium carbonate and sodium carbonate; amines such as ammonia or monomethylamine, dimethylamine, monoethylamine, diethylamine, and ethylenediamine; and quaternary ammonium hydroxides such as tetramethylammonium hydroxide. Among these, ammonia is most suitable from the perspective of excellent solubility in water, excellent catalytic activity, and easy removal from the powder through volatilization; a commercially available ammonia aqueous solution (concentration 25% by weight) can be used. Regarding the amount of ammonia solution added, relative to a total of 100 parts by mass of the silane compound or organopolysiloxane (e.g., components (a1) and (a2) above) used as raw materials for silicone rubber particles, the amount of 25% ammonia solution can be 80 to 1,000 parts by mass, preferably 200 to 800 parts by mass. If the amount of ammonia is insufficient, the condensate of the organoalkoxysilane will not adhere to the silicone rubber particle composite microparticles, and homogeneous silane particles may be formed.

[0051] (C) The organoalkoxysilane may be, for example, a trialkoxysilane represented by the following general formula (2) or a tetraalkoxysilane represented by the following general formula (3). R 2 Si(OR 3 )3 (2) Si(OR 3 )4 (3) In equations (2) and (3) above, R 2 For monovalent hydrocarbon groups having 1 to 20 carbon atoms, examples include: For the aforementioned R 1 The example is a monovalent hydrocarbon group. R 2 Preferably, it is an alkyl group having 1 to 10 carbon atoms, more preferably 1 to 5 carbon atoms. R 3 It is an alkyl group with 1 to 6 carbon atoms, such as methyl, ethyl, propyl, or butyl.

[0052] Examples of organotrialkoxysilanes represented by formula (2) above include: methyltrimethoxysilane, methyltriethoxysilane, methyltripropoxysilane, methyltributoxysilane, ethyltrimethoxysilane, propyltrimethoxysilane, and butyltrimethoxysilane. Examples of organotetraalkoxysilanes represented by formula (3) above include: tetramethoxysilane, tetraethoxysilane, etc. Among these, methyltrimethoxysilane is preferred.

[0053] Regarding the amount of (C) organoalkoxysilane condensate in the silicone rubber composite microparticles, the amount of (C) organoalkoxysilane condensate relative to 100% by mass of the silicone rubber composite microparticles is 0.1% to 80% by mass, preferably 10% to 80% by mass, and more preferably 10% to 40% by mass.

[0054] In the manufacture of the silicone rubber composite microparticles of the present invention, the amount of organoalkoxysilane blended relative to 100 parts by mass of water in the aqueous dispersion of the composite microparticles can be 0.1 to 100 parts by mass, preferably 5 to 30 parts by mass. If the amount of organoalkoxysilane (C) is too large, lumps may be formed, which is therefore not preferred. In addition, if the stirring is too vigorous during hydrolysis and condensation, especially when the amount of organoalkoxysilane is large, there is a tendency for the particles to agglomerate or fuse together. Therefore, it is preferable to stir under the mildest possible conditions. As the stirring device used, propeller blades, flat blades, anchor-type stirring blades, etc. are generally suitable. It should be noted that the reaction temperature during hydrolysis and condensation can be set in the range of 0 to 60°C, especially 5 to 20°C. This is because if the reaction temperature is below 0°C, the liquid will solidify, and if it is above 60°C, particles consisting only of the generated hydrolysis condensate will be formed, which will cause the particles to agglomerate or fuse together.

[0055] During the hydrolysis and condensation reactions of the aforementioned organoalkoxysilanes, alkaline substances or alkaline aqueous solutions can be added simultaneously with the organoalkoxysilanes or added afterward. Furthermore, when the amount of organoalkoxysilane added is large, it is preferable to pre-add the alkaline substances or alkaline aqueous solutions to the aqueous dispersion of the composite particles. While organoalkoxysilanes can be added to the reaction system all at once, in large quantities, this can sometimes lead to particle aggregation or fusion; therefore, it is preferable to add them slowly in small amounts each time.

[0056] Regarding stirring during the hydrolysis and condensation reactions, this stirring can continue for a period of time after the addition of the aforementioned organoalkoxysilanes and before the hydrolysis and condensation reactions are complete. Additionally, heating can be performed to complete the hydrolysis and condensation reactions, and acidic substances can be added for neutralization if necessary. Thus, the surface of the silicone rubber composite microparticles is coated with the hydrolysis condensate of the organoalkoxysilanes. After the reaction is complete, the dispersion can be concentrated by methods such as heating dehydration, filtration, centrifugation, or decantation. Then, it can be washed with water as needed, and moisture can be removed by heating and drying under normal or reduced pressure, spray drying by spraying the dispersion into an airflow, or heating and drying using a flowing heat medium. If the resulting silicone composite microparticles exhibit slight agglomeration, a pulverizer such as a jet mill, ball mill, or hammer mill can be used for crushing.

[0057] thermosetting resin composition The present invention also provides a thermosetting resin composition comprising a thermosetting resin and the above-mentioned silicone rubber composite microparticles. The amount of the silicone rubber composite microparticles mixed with 100 parts by weight of the thermosetting resin can be 0.5 to 80 parts by weight, preferably 2 to 50 parts by weight.

[0058] Thermosetting resins refer to compounds having reactive functional groups that form cross-linked structures and cure the resin layer. Examples of such thermosetting resins include acrylate compounds, epoxy compounds, bismaleimide compounds, cyanate ester compounds, and phenolic compounds. From the viewpoint of the viscosity of the resin layer and the coefficient of thermal expansion of the cured thermosetting composition, at least one of acrylate compounds, epoxy compounds, bismaleimide compounds, and phenolic compounds is preferred; more preferably, at least one of acrylate compounds, epoxy compounds, and bismaleimide compounds is preferred; and from the viewpoint of curing speed, at least one of acrylate compounds and epoxy compounds is even more preferred. These thermosetting resins can be used alone or in combination of two or more. Epoxy resins are particularly preferred.

[0059] There are no particular restrictions on the epoxy resin used, as long as it is an epoxy resin commonly used in thermosetting resin compositions, especially epoxy resin compositions for sealing. Examples include: epoxidation of phenolic varnish resins obtained by condensing or co-condensing phenolic resins (represented by phenolic varnish epoxy resins, o-cresol phenolic varnish epoxy resins, and epoxy resins with a triphenylmethane skeleton) with phenolic resins, cresol, xylenol, resorcinol, catechol, bisphenol A, bisphenol F, etc., and / or naphthols (α-naphthol, β-naphthol, dihydroxynaphthol, etc.) with aldehyde compounds (formaldehyde, acetaldehyde, propionaldehyde, benzaldehyde, salicylaldehyde, etc.) under an acidic catalyst; diglycidyl ethers (bisphenol type epoxy resins) such as bisphenol A, bisphenol F, bisphenol S, etc.; diglycidyl ethers (biphenyl type epoxy resins) such as alkyl-substituted or unsubstituted biphenyl phenols; stilbene type epoxy resins; hydroquinone type epoxy resins; and epoxy resins obtained by epoxidation of phenolic varnish epoxy resins (represented by phenolic varnish epoxy resins, o-cresol phenolic varnish epoxy resins, and epoxy resins with a triphenylmethane skeleton) with aldehyde compounds (formaldehyde, acetaldehyde, propionaldehyde, benzaldehyde, salicylaldehyde, etc.); bisphenol A, bisphenol F, bisphenol S, etc.; diglycidyl ethers (bisphenol type epoxy resins); alkyl-substituted or unsubstituted biphenyl phenols, etc.; diglycidyl ethers (biphenyl type epoxy resins); stilbene type epoxy resins; hydroquinone type epoxy resins; and epoxy resins obtained by condensation or co-condensation of phenolic varnish epoxy resins with a triphenylmethane skeleton under an acidic catalyst; phenolic varnish epoxy resins (represented by phenolic varnish epoxy resins, o-cresol phenolic varnish epoxy Epoxy resins include glycidyl ester type epoxy resins obtained by reacting polybasic acids such as phthalic acid and dimer acids with epichlorohydrin; glycidylamine type epoxy resins obtained by reacting polyamines such as diaminodiphenylmethane and isocyanuric acid with epichlorohydrin; epoxides of co-condensed resins of dicyclopentadiene and phenols (dicyclopentadiene type epoxy resins); epoxy resins containing naphthalene rings (naphthalene type epoxy resins); aralkyl type phenolic resins synthesized from phenols and / or naphthols with dimethoxy-p-xylene or bis(methoxymethyl)biphenyl; epoxides of aralkyl type phenolic resins such as naphthol-aralkyl resins; trimethylolpropane type epoxy resins; terpene-modified epoxy resins; linear aliphatic epoxy resins obtained by oxidizing alkene bonds with peracetic acid such as peracetic acid; alicyclic epoxy resins; and epoxy resins containing sulfur atoms. These epoxy resins can be used alone or in combination of two or more.

[0060] There is no particular limitation on the content of thermosetting resin in the thermosetting resin composition. From the viewpoint of obtaining sufficient curability, the content is preferably 30% by mass or more, more preferably 40% by mass or more, relative to the mass of the solid component of the thermosetting resin composition. From the viewpoint of the fluidity of the resin layer, the content of thermosetting resin is preferably 99% by mass or less, more preferably 95% by mass or less, and even more preferably 70% by mass or less, relative to the mass of the solid component of the resin layer or the thermosetting resin composition.

[0061] Furthermore, the thermosetting resin composition preferably further comprises a curing agent. The curing agent is not particularly limited to any curing agent commonly used in thermosetting resin compositions, especially in sealing epoxy resin compositions. Examples include: phenolic varnish-type phenolic resins obtained by condensing or co-condensing phenolic compounds such as phenol, cresol, resorcinol, catechol, bisphenol A, bisphenol F, phenylphenol, and aminophenol, and / or naphthols such as α-naphthol, β-naphthol, and dihydroxynaphthol with aldehyde-containing compounds such as formaldehyde, benzaldehyde, and salicylaldehyde under an acidic catalyst; and phenolic varnish-type phenolic resins obtained by condensing or co-condensing phenolic compounds and / or naphthols with dimethoxy-p-xylene or bis(methoxymethyl)biphenyl. Synthetic phenol-aralkyl resins; naphthol-aralkyl resins and other aralkyl-type phenolic resins; copolymer phenol-aralkyl resins with a phenol-phenolic varnish structure that is randomly, blockly, or alternately repeated with the phenol-aralkyl structure; p-xylene and / or m-xylene modified phenolic resins; melamine modified phenolic resins; terpene modified phenolic resins; dicyclopentadiene type phenolic resins; cyclopentadiene type phenolic resins; polycyclic aromatic ring modified phenolic resins, etc. These curing agents can be used alone or in combination of two or more.

[0062] Furthermore, the thermosetting resin composition of the present invention may be mixed with a curing accelerator for promoting the curing reaction between the thermosetting resin and the curing agent, and various inorganic fillers such as fused silica, crystalline silica, alumina, magnesium oxide, magnesium silicate, and aluminum. Moreover, without impairing the effects of the present invention, other known additives that are incorporated into the thermosetting resin composition may also be appropriately mixed in.

[0063] The method for manufacturing the thermosetting resin composition of the present invention can be carried out according to conventionally known methods. For example, it can be obtained by mixing the above-mentioned components according to conventional methods. The thermosetting resin composition of the present invention containing silicone composite microparticles, and particularly preferably epoxy resin composition, is excellent from the viewpoint of stress relief as a sealing material. Therefore, the thermosetting resin composition of the present invention can be used as a constituent material for prepregs, single-layer resin sheets, laminated resin sheets, metal foil laminates, printed wiring boards, and semiconductor packages. For example, a prepreg can be obtained by impregnating or coating a solution obtained by dissolving the composition of the present embodiment in a solvent onto a substrate and drying it. In addition, by using a peelable plastic film as a support, coating the solution obtained by dissolving the composition of the present embodiment in a solvent onto the plastic film and drying it, a buildup film or dry film solder resist can be obtained. Furthermore, it is useful as a sealing material for semiconductor components, etc., and can be applied to an object, such as an electronic circuit board, by a known coating method, and is suitable as a sealing material. Example

[0064] The present invention will be described in more detail below with examples and comparative examples, but the invention is not limited to the examples described below. It should be noted that in the examples below, parts and % represent parts by mass and percentage by mass, respectively.

[0065] Manufacturing of composites containing silicone rubber particles and inorganic powders [Manufacturing Example 1] 56g of methylvinylsiloxane (kinematic viscosity 8.5 mm) represented by formula (1) was added to a 0.5-liter glass beaker. 2 / s, vinyl value 0.21 (mol / 100g)), 16g of methylhydropolysiloxane represented by the following formula (2) (kinematic viscosity 121mm) 2 The mixture (H value 0.85 mol / 100g) was stirred at 2,000 rpm using a homogenizer. Then, 0.22g of polyoxyethylene lauryl ether (addition molar number = 9 mol), 38g of water, and 16g of boron nitride (SP-3, manufactured by DENKA Corporation) were added, and stirring continued at 8,000 rpm. Phase inversion occurred, confirming thickening. After dilution with 240g of dilution water, a silicone oil emulsion as an O / W type emulsion was obtained.

[0066] Next, the silicone oil emulsion was transferred to a glass flask equipped with an anchor-type stirring device, and a mixture of 0.84 g of a toluene solution (0.5% platinum content) of chloroplatinic acid-olefin complex and 1.92 g of polyoxyethylene (addition molar number = 9 mol) lauryl ether was added at room temperature with stirring. The reaction was carried out for 12 hours, resulting in an aqueous dispersion of the composite (microparticles). The solids content was approximately 21%.

[0067] (n=10.5) (m=48, n=50).

[0068] [Manufacturing Example 2] 56g of methylvinylsiloxane (kinematic viscosity 8.5mm) represented by formula (1) was added to a 0.5-liter glass beaker. 2 / s, vinyl value 0.21 (mol / 100g)), 16g of the methylhydropolysiloxane represented by the above formula (2) (kinematic viscosity 121mm) 2 The mixture (pH value 0.85 mol / 100g) was stirred at 2,000 rpm using a homogenizer. Then, 38g of water and 4g of boron nitride (SP-3, manufactured by DENKA Corporation) were added, and stirring continued at 8,000 rpm. Phase inversion occurred, confirming thickening. After dilution with 240g of water, a silicone oil emulsion as an O / W type emulsion was obtained.

[0069] Next, the silicone oil emulsion was transferred to a glass flask equipped with an anchor-type stirring device, and 0.84 g of a toluene solution of chloroplatinic acid-olefin complex (0.5% platinum content) was added at room temperature with stirring. The reaction was carried out for 12 hours, resulting in an aqueous dispersion of the complex (microparticles). The solid content was approximately 21%.

[0070] [Manufacturing Example 3] 56g of methylvinylsiloxane (kinematic viscosity 8.5mm) represented by formula (1) was added to a 0.5-liter glass beaker. 2 / s, vinyl value 0.21 (mol / 100g)), 16g of the methylhydropolysiloxane represented by the above formula (2) (kinematic viscosity 121mm) 2 The mixture (H value 0.85 mol / 100g) was stirred at 2,000 rpm using a homogenizer. Then, 38g of water and 24g of boron nitride (SP-3, manufactured by DENKA Corporation) were added, and stirring continued at 8,000 rpm. Phase inversion occurred, confirming thickening. After dilution with 240g of dilution water, a silicone oil emulsion as an O / W type emulsion was obtained.

[0071] Next, the silicone oil emulsion was transferred to a glass flask equipped with an anchor-type stirring device, and 0.84 g of a toluene solution of chloroplatinic acid-olefin complex (0.5% platinum content) was added at room temperature with stirring. The reaction was carried out for 12 hours, resulting in an aqueous dispersion of the complex (microparticles). The solid content was approximately 21%.

[0072] [Comparative Manufacturing Example 1] 56g of methylvinylsiloxane (kinematic viscosity 8.5mm) represented by formula (1) was added to a 0.5-liter glass beaker. 2 / s, vinyl value 0.21 (mol / 100g)), 16g of the methylhydropolysiloxane represented by the above formula (2) (kinematic viscosity 121mm) 2 The mixture (H value 0.85 mol / 100g) was stirred at 2,000 rpm using a homogenizer. Then, 0.22 g of polyoxyethylene lauryl ether (addition molar number = 9 mol) and 38 g of water were added, and stirring continued at 8,000 rpm. Phase inversion occurred, confirming thickening. After dilution with 240 g of diluent, a silicone oil emulsion as an O / W type emulsion was obtained.

[0073] Next, the silicone oil emulsion was transferred to a glass flask equipped with an anchor-type stirring device, and a mixture of 0.84 g of a toluene solution of chloroplatinic acid-olefin complex (platinum content 0.5%) and 1.92 g of polyoxyethylene (addition molar number = 9 mol) lauryl ether was added at room temperature with stirring. The reaction was carried out for 12 hours, resulting in an aqueous dispersion of microparticles. The solid content was approximately 21%.

[0074] [Examples 1-3, Comparative Example 1] Manufacturing of silicone rubber composite microparticles 200g of water, 182g of an aqueous dispersion of the composite obtained in Manufacturing Examples 1-3 or an aqueous dispersion of the microparticles obtained in Comparative Manufacturing Example 1 (both with a solid content of approximately 21%), and 19.6g of ammonia water (concentration 25% by weight) were added to a 500ml glass flask. The water temperature was set to 10°C, and the mixture was stirred using an anchor-type stirrer at a blade speed of 150 rpm. The pH of the dispersion at this time was 12.7. While maintaining the liquid temperature at 5-15°C, 18g of methyltrimethoxysilane (KBM-13, manufactured by Shin-Etsu Chemical Industry Co., Ltd.) was added dropwise over 20 minutes, and the mixture was stirred for 1 hour. Afterward, the mixture was heated to 55-60°C and stirred for another hour. The resulting reaction solution was filtered to form a cake, dried at 55°C for at least 16 hours, and then jet-milled to obtain silicone rubber composite microparticles.

[0075] The blending ratios (parts by mass) of each component in Examples 1-3 and Comparative Example 1, and the average particle size based on volume of the resulting silicone rubber composite microparticles are recorded in Table 1. The method for determining the average particle size is as described above.

[0076] [Table 1] [Examples 4-6, Comparative Examples 2-4] Preparation of thermosetting resin compositions A thermosetting resin composition was obtained by adding epoxy resin, curing agent, and silicone rubber microparticles obtained in the above examples according to the composition and mixing amounts shown in the table below. The thermosetting resin composition was cured according to the method described below. Bending tests and dielectric loss tangent measurements were performed on each cured product. The results are shown in Table 2.

[0077] It should be noted that the epoxy resin and curing agent used in the examples and comparative examples are shown below.

[0078] • A mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin: ZX-1059 (Epoxy equivalent: 160-170, viscosity (25℃): 1900~2600 mPa·s, manufactured by Nippon Steel Chemical Materials Co., Ltd.) • The aromatic amine catalyst represented by the following formula: KAYAHARD AA (manufactured by Nippon Kayaku Co., Ltd.) The determination methods and conditions are as follows.

[0079] [Bending Test] After mixing the various thermosetting resin compositions for 10 minutes, vacuum degassing was performed at 60°C, and the mixture was injected into a 4mm thick mold. After heating at 150°C for 4 hours, the mixture was cooled and opened. The resulting cured material was cut to the following dimensions using a diamond cutter, and a bending test was conducted to determine the flexural modulus (MPa). This bending test was performed according to JIS K7171 using an Autograph (manufactured by Shimadzu Corporation). The test conditions were: distance between support points 64mm, speed 2mm / min, and sample thickness 4mm. The flexural modulus is preferably less than 2,700MPa.

[0080] [Dielectric loss tangent] The dielectric constant and dielectric loss tangent at 60 GHz were determined using a network analyzer via the free-space method. The dielectric loss tangent is preferably less than 0.029.

[0081] [Table 2] As shown in Table 2, the silicone rubber composite microparticles of the present invention possess the flexibility of silicone rubber and impart a low dielectric loss tangent to the cured product. Furthermore, by incorporating the silicone rubber composite microparticles containing boron nitride into the thermosetting resin composition, a cured product with a lower flexural modulus and greater flexibility can be supplied compared to a cured product obtained by incorporating only boron nitride into the thermosetting resin composition (Comparative Example 3).

[0082] Industrial applicability Compared to conventional silicone rubber microparticles, the silicone rubber composite microparticles of the present invention provide thermosetting resin compositions, as well as single-layer resin sheets, laminated resin sheets, prepregs, metal-coated foil laminates, printed wiring boards, sealing materials, fiber-reinforced composite materials, and adhesives. These compositions reduce the flexural modulus of the cured material and impart a low dielectric constant and a low dielectric loss tangent to the cured material. This thermosetting resin composition is useful as a sealing material for semiconductor components, etc., and can be applied to an object, such as an electronic circuit board, using known coating methods, and is suitable for use as a sealing material.

Claims

1. A silicone rubber composite microparticle, comprising silicone rubber composite microparticles having an average particle size of 0.1~100μm, and including: A composite containing (A) silicone rubber particles and (B) at least one inorganic powder selected from silicon dioxide, boron nitride, and aluminum nitride; and (C) Condensates of organoalkoxysilanes.

2. The silicone rubber composite microparticles according to claim 1, wherein, Relative to 100% by mass of the silicone rubber composite microparticles, it comprises: 0.1~80% by mass of (A) silicone rubber granules; 0.1 to 80% by mass of (B) is selected from at least one inorganic powder selected from silicon dioxide, boron nitride and aluminum nitride; as well as Condensates of (C) organoalkoxysilanes, ranging from 0.1% to 80% by mass.

3. The silicone rubber composite microparticles according to claim 1, wherein, The silicone rubber of component (A) has the structure represented by the following formula (1). -(R 1 2SiO) a - (1) In the above formula (1), R 1 Each group consists of a substituted or unsubstituted monovalent hydrocarbon group having 1 to 20 carbon atoms, and a is an integer from 5 to 5,000.

4. The silicone rubber composite microparticles according to claim 1, wherein, The (C) organoalkoxysilane is selected from at least one of the following general formulas: trialkoxysilanes represented by (2) and tetraalkoxysilanes represented by (3). R 2 Si(OR 3 )3 (2) Si(OR 3 )4 (3) In equations (2) and (3) above, R 2 R is a monovalent hydrocarbon group with 1 to 20 carbon atoms. 3 It is an alkyl group having 1 to 6 carbon atoms.

5. The silicone rubber composite microparticles according to claim 1, wherein, The silicone rubber composite microparticles are composed of the following components: (A) a composite of silicone rubber particles and (B) at least one inorganic powder selected from silicon dioxide, boron nitride and aluminum nitride, and (C) a condensate of an organoalkoxysilane.

6. A thermosetting resin composition comprising a thermosetting resin and silicone rubber composite microparticles according to any one of claims 1 to 5, wherein, The amount of the silicone rubber composite microparticles is 0.5 to 80 parts by weight relative to 100 parts by weight of the thermosetting resin.

7. A cured product formed by curing the thermosetting resin composition according to claim 6.

8. A semiconductor element sealed with the cured material according to claim 7.

9. A method for manufacturing silicone rubber composite microparticles, the method comprising: The process of mixing (A') a curable organopolysiloxane composition, (B) at least one inorganic powder selected from silica, boron nitride and aluminum nitride, water and optional surfactant, and curing the curable organopolysiloxane composition to obtain an aqueous dispersion of the composite. as well as The process involves hydrolyzing and condensing (C) organoalkoxysilanes in the aqueous dispersion of the composite obtained in the process to obtain silicone rubber composite microparticles with an average particle size of 0.1 to 100 μm.

10. The method for manufacturing silicone rubber composite microparticles according to claim 9, wherein, Relative to a total of 100 parts by mass of the organopolysiloxane, (B) inorganic powder and (C) organoalkoxysilane in component (A'), the amount of component (B) is 0.1 to 80 parts by mass, and the amount of organoalkoxysilane (C) is 0.1 to 80 parts by mass.

11. The method for manufacturing silicone rubber composite microparticles according to claim 9, wherein, The (A') cured organopolysiloxane composition is a condensation reaction cured organopolysiloxane composition, a free radical reaction cured organopolysiloxane composition, or an addition reaction cured organopolysiloxane composition.

12. The method for manufacturing silicone rubber composite microparticles according to claim 9, wherein, The (C) organoalkoxysilane is selected from at least one of the following general formulas: trialkoxysilanes represented by (2) and tetraalkoxysilanes represented by (3). R 2 Si(OR 3 )3 (2) Si(OR 3 )4 (3) In equations (2) and (3) above, R 2 R is a monovalent hydrocarbon group with 1 to 20 carbon atoms. 3 It is an alkyl group having 1 to 6 carbon atoms.

Citation Information

Patent Citations

  • Thermosetting epoxy resin composition

    JP1996085753A

  • Additive for epoxy resin and epoxy resin composition

    JP2007023061A

  • Epoxy resin composition for sealing and electronic part device by using the same

    JP2007146148A

  • Solid sealing material for compression molding, semiconductor device, and semiconductor device production method

    JP2018172545A

  • Epoxy-modified silicone fine particles and method for producing the same, thermosetting resin composition containing the fine particles, and sealing material

    JP2021075605A